Comparative transcriptomics analysis at the key stage of maize ear development dissect heterosis. Issue 1 (7th December 2022) - Wang, Liangfa; Li, Juan; Lin, Yuan; Dang, Kuntai; Wan, Jiong; Meng, Shujun; Qiu, Xiaoqian; Wang, Qiyue; Mu, Liqin; Ding, Dong; Luo, Hongbing; Tang, Jihua
Abstract: Important traits related to maize ( Zea mays L.) grain yield, such as kernel row number, ear length, kernel number per row, are determined during the development of female inflorescence. There is a significant positive correlation between yield component and the activity of inflorescence meristem (IM). To find the key stage of heterosis in the development of the ear, immature ears (from the IM stage until the end of the floral meristem [FM] stage) of Yudan888 and its parent lines were sampled to assay phenotype and for comparative transcriptomics analysis. The immature ear length of Yudan888 at the IM stage fitted an additive (mid‐parental) model, but it showed high parental dominance at the spikelet‐pair meristem (SPM) stage. Comparative analysis of transcriptomes suggested significant differences between additive and nonadditive expression patterns for different developmental stages. The number of distinct maternal or paternal genes (DMP) (genes expressed only in one parental line and their hybrid but silenced in another line) was greater than ABF1 (genes expressed in both parental lines but silenced in hybrid) at each stage. Gene Ontology (GO) enrichment suggested that the cell redox homeostasis genes with overdominance expression patterns in hybrids have an important contribution to heterosis. According to our research, an ear length heterosis network was established. The discovery of the inflection point for ear length heterosis allows us for inferring that the transition state of IM to SPM may be the starting point of ear length heterosis. These findings improved the understanding of maize ear length heterosis. Core Ideas: The spikelet‐pair meristem period is the inflection point of heterosis of ear length. The distinct maternal or paternal genes may produce epistasis, leading to a nonadditive expression pattern. Nonadditive expression made the hybrid show stronger vigor than both parents. Cell redox homeostasis genes that maintain overdominant expression may have an important contribution to heterosis An ear length heterosis network is described according to the study.